A NEW PARADIGM OF ISLAMIC EDUCATION ON LOCAL AND GLOBAL PERSPECTIVE - Mubin, Holikul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Problems related to Islamic education still exist for study. Islamic education issues such as lack of competition, dualism of education, quality of learning, and new paradigms or new ideas of Islamic education based on local and global perspectives are very interesting to examine. This study aims to determine local and global perspectives on the paradigm of Islamic education. This research uses qualitative research methods with a literature study approach. Based on the data that the researchers found, the new paradigm of Islamic education is defined as a new idea that continues to be developed through the Islamic education system by collaborating the use of science and technology but cannot be separated from the fundamental concepts, namely the Qur'an and Hadith and related to perspective, the local perspective views that the new paradigm of Islamic education has a positive impact on the development of science, technology and also the character of students, while the global (western) perspective states that Islamic education must continue to improve and improve the existing education system for the advancement of Islamic education itself, to achieve the goals of Islamic education.